Drug resistance in infectious diseases: modeling, parameter estimation and numerical simulation - Le Thi Thanh, An; Jäger, Willi (Model Based Parameter Estimation, 2013)
Infectious diseases are drawing our attention again. In recent years, we have been confronted with SARS, bird-flu, swine-flu and many other severe diseases. In addition, pathogens are getting resistant to drugs controlling them. In this paper we establish a new population dynamical system of infectious diseases including drug treatment. We take into account both sensitive and resistant parasites. The unknown model parameters are fitted based on a set of data for malaria from Cisse, Burkina Faso. The fitted model is used to investigate the influence of drug treatment on drug resistance. Based on these investigations, treatment strategies to reduce drug resistance can be elaborated.